Contemporary state terrorism: theory and practice - Jackson, Richard (Critical terrorism studies, 2010)
Introduction: terrorism, the state and the study of political terror / Richard Jackson..., et al. -- State terrorism in the social sciences: theories, methods and concepts / Ruth Blakeley -- Darfur's dread: contemporary state terrorism in the Sudan / David Mickler -- State terrorism and the military in Pakistan / Eamon Murphy and Aazar Tamana -- Israel's other terrorism challenge / Sandra Nasr -- "We have no orders to save you": state terrorism, politics and communal violence in the Indian state of Gujarat, 2002 / Eamon Murphy -- The politics of convenient silence in southern Africa: relocating the terrorism of the state / Joan Wardrop -- Revenge and terror: the destruction of the Palestinian community in Kuwait / Victoria Mason -- Winning hearts and mines: the Bougainville crisis, 1988-90 / Kristian Lasslett -- Paramilitarism and state terror in Colombia / Sam Raphael -- "We are all in Guantanamo": state terror and the case of Mamdouh Habib / Scott Poynting -- From garrison state to garrison planet: state terror, the War on Terror and the rise of a global carceral complex / Jude McCulloch -- The deterrence logic of state warfare: Israel and the second Lebanon war, 2006 / Karine Hamilton -- Conclusion: contemporary state terrorism--towards a new research agenda / Richard Jackson